Self-Confidence Among Football Players in the first Division League in the Kingdom of Saudi Arabia - Faqihi , Mohammed (Journal of Physical Education, 2025)
This study aimed to identify the levels of self-confidence among football players in the first division league in the Kingdom of Saudi Arabia, in addition to the differences in the levels of self-confidence among the study sample according to the variable of training experience. The study sample amounted to (100) players who were selected randomly. The researcher used the descriptive approach for its suitability to the nature of the study. In this study, the self-confidence scale was applied, which was built and standardized by both Qawasmi and Al-Farah (1996). The most important results indicated that the highest average of the dimensions of the self-confidence scale among football players under study was in the dimension (psychological aspect), which came at a rate of (73.47%), while the lowest average of the dimensions of the scale was in favor of the physiological aspect at a rate of (47.01%). Regarding the differences in the levels of self-confidence according to the variable of training experience, the results indicated the existence of statistically significant differences at the level (0.05) in the dimensions (independence - psychological aspect - physiological aspect) in favor of players whose experience ranged between 10 years and more. Through the results of the study, the researcher recommends the need to pay attention to psychological preparation programs that help raise the level of self-confidence, and that this should start from the early age players.